RESPON MASYARAKAT TERHADAP PELAKSANAAN PROGRAM KELUARGA HARAPAN DI KECAMATAN MEDAN SELAYANG - GRACE LELIHARNI DAMANIK (Welfare StatE, 2013)
In community development in Indonesia, poverty is one of the main problem that marked by amount of impecunious society, unemployment, backwardness and powerless. The height  number of impecunious society cause degradation of human resource happened and make  energy emulation of nation progressively weaken. By paying attention from the condition  above, the government released policy of program which represent development of social security system able to lighten and assist household very impecunious to getting  access service of health and elementary education with the expectation of this program can decrease poverty in our state. The program is Family Expectation Program. This study aims to know the response community to execution of Family Expectation Program In Kecamatan Medan Selayang which seen from 3 aspects that is perception, participation and attitude. This is a descriptive study which aims to give a sense or delineating exixsting reality of the community or group of people certain in field in the analysis that process is covering the decipherment the observation of one symptom observed or more, with population of as many as 164 people. In this case, data from all population is taken. Data analysis techniques using a single table and described in qualitative and quantitative analysis by using a Likert scale to measure perceptions, attitudes and participation of the community to the Family Expectation Program. Results of data analysis showed that the community have a positive perception to Family Expectation Program with the value of 0,87 which seen from knowledge of community about Family Expectation Program and also the target and benefits from this program. Community attitude to Family Expectation Program is positive with a value of 0,91 seen from comments and assessment of community who agree with implementation of Family Expectation Program and assess this program useful for increasing the prosperity of community. Participation of community to Family Expectation Program is positive with a value of 0,92 which seen from involvement and livelines of community in each activity of meeting and obligation of community as participant of Family Expectation Program. Based on the results of data analysis can be concluded that the response of  community to the Family Expectation Program is positive.   Key Words : Response Community,  Family Expectation Program